2018
DOI: 10.1371/journal.pone.0202734
|View full text |Cite
|
Sign up to set email alerts
|

Socio-economic determinants of anemia in pregnancy in North Shoa Zone, Ethiopia

Abstract: BackgroundGlobally, anemia in pregnancy increases maternal, fetal and neonatal mortality and morbidity. According to 2011 Ethiopian Demographic and Health Survey, 22% of pregnant women in Ethiopia were reported to be anemic. However, since the Ethiopian population is diverse with regard to culture, religion and other characteristics, this evidence may not represent the condition in our study area. So, we aimed to determine the prevalence of anemia and its associated factors among women receiving Antenatal Care… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
36
2
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(49 citation statements)
references
References 11 publications
5
36
2
6
Order By: Relevance
“…Pregnant women having parasitic infestation were nearly 12 times AOR = 11.886(95% CI 5.606, 25.204) more likely to be anemic than their counterparts. This nding is consistent with studies conducted in Gondar (28), Shire 14, Adigrat (27), and North Shoa (9). This might be due to the reason that parasites attach and injure upper intestinal mucosa and ingest blood.…”
Section: Magnitude Of Anemia In Pregnant Womensupporting
confidence: 91%
See 2 more Smart Citations
“…Pregnant women having parasitic infestation were nearly 12 times AOR = 11.886(95% CI 5.606, 25.204) more likely to be anemic than their counterparts. This nding is consistent with studies conducted in Gondar (28), Shire 14, Adigrat (27), and North Shoa (9). This might be due to the reason that parasites attach and injure upper intestinal mucosa and ingest blood.…”
Section: Magnitude Of Anemia In Pregnant Womensupporting
confidence: 91%
“…The possible reasons for the difference may be resulted from geographical variation of factors across different areas. In addition, lower magnitude can be attributed to gradual improvement of life style and living standards, using the iron supplementation ordered by the physician during follow up (23) This study nding showed a slightly higher magnitude than studies conducted in Hawassa (15.3%) (24) ,Tikur Anbesa Specialized Hospital (14.1%) (25), Adama town (11.3%) (26), North Shoa zone (9.7%) (9) and Adigrat General Hospital 7.9% (27). This variation might be due to differences in sample size, study design, study period, study setting, and socio-demographic characteristics.…”
Section: Magnitude Of Anemia In Pregnant Womenmentioning
confidence: 65%
See 1 more Smart Citation
“…But we did not find any mean value difference of hemoglobin levels across education and occupation. 9 Belachew T et al found that the prevalence of anemia was 38.2%. They also observed that the mean value of the hemoglobin was 11.3 gm/dl.…”
Section: Discussionmentioning
confidence: 99%
“…According to literatures the predisposing factors for anemia in pregnant women include, socioeconomic status, Parasitic Infestation (Malaria and Helminthes), and obstetric condition (5).The cutoff point suggested by United States Center for Diseases Control to determine anemia is when a hemoglobin level is less than 11g/dl in the first and third trimester and less than 10.5 g/dl in the second trimester of pregnancy (6).The World Health Organization (WHO) defined anemia as hemoglobin concentration below 11g/dl in pregnancy and will classify as mild, moderate and severe (7).The estimated global magnitude is 42% in pregnant women and it is a major cause of maternal mortality (8). In Africa 57.1% of the pregnant women were Anemic, more over anemia in pregnant women is a sever public health problem, in Ethiopia 29% and also different studies were conducted on magnitude of anemia among pregnant women, the magnitude range being from 9.7% in North Shoa Zone to 56.8% in Eastern Ethiopia (9). Studying the specific etiology and magnitude of anemia in a given setting and population group is very important to prevent or treat anemia (10).However, there is very little data available in the study area.…”
Section: Introductionmentioning
confidence: 99%